2018
DOI: 10.1136/bjsports-2017-098827
|View full text |Cite
|
Sign up to set email alerts
|

Walking on sunshine: scoping review of the evidence for walking and mental health

Abstract: The evidence base that suggests walking benefits mental health is growing, but remains fragmented and incomplete for some important outcomes. Policy and national guidelines should promote the known mental health benefits of increased walking and future research should directly address the gaps we have identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(118 citation statements)
references
References 87 publications
6
97
0
2
Order By: Relevance
“…There has been some evidence to support that, compared to physical inactivity, engaging in physical activity levels less than those recommended and increased light intensity physical activity, may convey mental health benefits [28,37]. One accelerometry-based study demonstrated using isotemporal substitution models that substituting 30 min of light intensity physical activity for 30 min of sedentary time (while holding total wear time Table 3 Odds ratios (OR) and 95% confidence intervals (CI) derived from binominal logistic regression analyses as indicators of cross-sectional associations between physical activity (PA) and anxiety within sex categories and the total population…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been some evidence to support that, compared to physical inactivity, engaging in physical activity levels less than those recommended and increased light intensity physical activity, may convey mental health benefits [28,37]. One accelerometry-based study demonstrated using isotemporal substitution models that substituting 30 min of light intensity physical activity for 30 min of sedentary time (while holding total wear time Table 3 Odds ratios (OR) and 95% confidence intervals (CI) derived from binominal logistic regression analyses as indicators of cross-sectional associations between physical activity (PA) and anxiety within sex categories and the total population…”
Section: Discussionmentioning
confidence: 99%
“…Given the worldwide promotion of the benefits of meeting these guidelines, it is important to clarify their association with anxiety symptoms and status. Furthermore, walking is an accessible behaviour for all ages and sexes that is known to confer many physical health benefits; however, just one longitudinal [36] and few cross-sectional [37] studies have examined associations of walking with anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Walking is a widely endorsed way to increase physical activity [5,8]. Walking is an accessible, low risk and inexpensive form of physical activity [8] that can prevent and treat non-communicable diseases [5], such as cardiovascular disease [9] and obesity [10,11], and improve mental health [12]. Whilst walking is the most common form of physical activity in the US and the UK [8,13,14], only half of adults in the US [15] and two-thirds of adults in the UK [16] meet the recommended levels of physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…The literature highlights that there are several theoretical hypotheses that have been proposed to explain how exposure to the natural environment may impact mental wellbeing [43,44], including the "Biophilia hypothesis" [45,46], Attention Restoration Theory (ART) [47] and "Psycho-evolutionary stress reduction theory" [48]. A recent systematic review of 5 systematic reviews and 50 individual papers suggests that walking benefits mental health [49]. There is also empirical evidence, summarised in systematic reviews, that being physically active outdoors has value-added mental health benefits to being active indoors [50,51].…”
Section: Resultsmentioning
confidence: 99%